SUBTITLING STRATEGIES IN DUNE MOVIE - Chintia Handayani (Asosiasi Dosen Muda Indonesia, 2022)
Subtitling strategies are strategies used by audio-visual translators in translating an audio-visual product into the subtitle form. This research aimed to find out the subtitling strategies used and the most strategies frequently used by EveryAgent in Dune movie. This research used theory by Henrik Gottlieb (1992). This research used qualitative method. The source data of this research is Dune movie, and the data of this research are the subtitles in Dune movie. The results of this research showed that there are 29 data of condensation, 5 data of decimation, 1 datum of deletion, 6 data of dislocation, 6 data of expansion, 50 data of imitation, 35 data of paraphrase, and 176 data of transfer. Based on those results, it can be concluded that transfer strategy is the most strategy applied in Dune movie.